Implementation of Selective Policy in Granting State Enterprises License Calling Visa in Anticipating Immigration Violations at Immigration Examinations - Ale Alfero Deputra; Bima Yosua A Tarigan (Polteknik Imigrasi, 2021)
State guests from calling visa countries come to Indonesia through the Immigration Checkpoint without a visa and are granted an entry permit on condition that they have clear recommendations. This policy is given based on the consideration of the competent authorities in order to support good bilateral cooperation between countries. The research method used is empirical normative legal research which is descriptive qualitative in nature by collecting data by collecting legal materials by identifying and analyzing laws and regulations, field data, library materials (books, scientific papers, articles), and other sources. other legal materials that are still relevant in this study. This research was conducted to determine the implementation of selective policies in granting entry permits for state guests (VVIP and VIP) from calling visas in anticipation of immigration violations at the Immigration Checkpoint and to find out the relationship between the selective policy and the applicable law. From the results of the study, it was found that the selective policy as a principle in granting entry permits for state guests calling visas still pays attention to the balance between the security approach and the welfare approach where the procedure is contained in the Regulation of the Minister of Law and Human Rights.